Financial and Health Diaries 2012-2013: A Year-long Weekly Panel of Farming Households in Nigeria and Kenya - Janssens, Wendy; Kramer, Berber; van der List, Marijn; Paper, David (Amsterdam Institute for Global Health and Development, 2019)
The Financial and Health Diaries capture high-detail high-frequency data on how low-income households in developing countries manage money and make spending choices around healthcare. The data provide detailed weekly information on individuals’ financial activities, health events and interactions with healthcare providers.